Analisis Pengaruh Islamicity Performance Index Terhadap Tingkat Profitabilitas Pada Bank Syariah Indonesia : Studi Kasus: Bank BUMN Syariah Yang di Merger - Nurya Ayu Destiani; Juliana Juliana; Aneu Cakhyaneu (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
This study aims to determine the level of profitability at BUMN Sharia Banks consisting of Bank Mandiri Syariah, BNI Syariah and BRI Syariah which were merged into Bank Syariah Indonesia (BSI) and the factors that influence it. The three state-owned Islamic banks have a level of profitability that does not meet healthy standards in the fairly healthy category. The independent variables used in this study include Profit Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), Equitable Distribution Ratio (EDR) and Islamic Income vs. Non-Islamic Income while the dependent variable is the level of profitability. The research method used is descriptive quantitative using Multiple Linear Regression analysis. The results of this study indicate that Profit Sharing Ratio (PSR) has a significant negative effect on the level of profitability of Islamic State-owned banks, Zakat Performance Ratio (ZPR) has a significant positive effect on the level of profitability of BUMN Sharia Banks, Equitable Distribution Ratio (EDR) has a significant negative effect on the level of profitability at BUMN Sharia Banks and Islamic Income vs. Non Islamic Income has no significant effect on the level of profitability of BUMN Sharia Banks. The implication of this research is to find out the extent to which at BUMN Sharia Banks can optimize financial performance with the factors that influence it, especially the ratio with Islamic principles. The still low standard of Islamicity Performance Index in each ratio is one of the causes of lessthan optimal profit growth at BUMN Sharia Banks.